Gradient disparities in allergy and the gut microbiome among rural, migrant, and urban populations across China - Wanjun Wang; Mo Xian; Ruchong Chen; Jing Li; Lulu Wu (World Allergy Organization Journal)
Background: While much of the evidence linking the rapid urbanization and the increasing prevalence of allergen sensitization, but little is known regarding rural-to-urban migrants. The aim of this study was to identify the disparities in allergy, the gut microbiome and factors among native urban, migrating, and native rural Chinese. Methods: We redesigned the dataset of the China Alliance of Research on Respiratory Allergic Disease secondary survey, and after stratified sampling, a subsample of 2422 subjects were enrolled for the analysis of a questionnaire, skin prick tests (SPT), and specific immunoglobulin E (sIgE) titer measurements against 8 common allergens. Fecal microbiotal composition was also sequenced by 16S rRNA and regression-based analyses with covariate adjustment applied. Results: From urban to migrant and rural populations, IgE sensitization was predominantly directed against Dermatophagoides pteronyssinus (Der p). The titers of Der p-sIgE decreased sequentially across the 3 respective populations and co-sensitization to other allergens also showed a sequential decrease. Rural-to-urban migrants showed a low prevalence of Der p-SPT and Der p-sIgE initially, but developed substantial IgE titers and their gut microbiotal diversity, as well as species richness, appeared to change along with residential time spent in the urban area. High-fat diet, using a mattress, an SPT wheal size from Der p ≥ 6 mm, and duration of immigration >5 years were significantly associated with sIgE positivity in the migrants. Conclusion: The Der p-sIgE responses and the composition of gut microbiota differs synchronously with extended living time in an urban area. Studies in immigrants provide a unique opportunities to evaluate the effects of environmental factors in the pathogenesis of allergic disorders.